Vesicular glutamate transporter modulates sex differences in dopamine neuron vulnerability to age‐related neurodegeneration. Issue 5 (28th April 2021) - Buck, Silas A.; Steinkellner, Thomas; Aslanoglou, Despoina; Villeneuve, Michael; Bhatte, Sai H.; Childers, Victoria C.; Rubin, Sophie A.; De Miranda, Briana R.; O'Leary, Emma I.; Neureiter, Elizabeth G.; Fogle, Keri J.; Palladino, Michael J.; et al.
Abstract: Age is the greatest risk factor for Parkinson's disease (PD) which causes progressive loss of dopamine (DA) neurons, with males at greater risk than females. Intriguingly, some DA neurons are more resilient to degeneration than others. Increasing evidence suggests that vesicular glutamate transporter (VGLUT) expression in DA neurons plays a role in this selective vulnerability. We investigated the role of DA neuron VGLUT in sex‐ and age‐related differences in DA neuron vulnerability using the genetically tractable Drosophila model. We found sex differences in age‐related DA neurodegeneration and its associated locomotor behavior, where males exhibit significantly greater decreases in both DA neuron number and locomotion during aging compared with females. We discovered that dynamic changes in DA neuron VGLUT expression mediate these age‐ and sex‐related differences, as a potential compensatory mechanism for diminished DA neurotransmission during aging. Importantly, female Drosophila possess higher levels of VGLUT expression in DA neurons compared with males, and this finding is conserved across flies, rodents, and humans. Moreover, we showed that diminishing VGLUT expression in DA neurons eliminates females' greater resilience to DA neuron loss across aging. This offers a new mechanism for sex differences in selective DA neuron vulnerability to age‐related DA neurodegeneration. Finally, in mice, we showed that the ability of DA neurons to achieve optimal control over VGLUT expression is essential for DA neuron survival. These findings lay the groundwork for the manipulation of DA neuron VGLUT expression as a novel therapeutic strategy to boost DA neuron resilience to age‐ and PD‐related neurodegeneration. Abstract : Dopamine neuron VGLUT mediates age‐ and sex‐related differences in dopamine neurodegeneration during aging. Female Drosophila, rats and humans express more VGLUT in dopamine neurons than males, and VGLUT knockdown in dopamine neurons diminishes sex differences in vulnerability to age‐related degeneration. The ability to finely tune dopamine neuron VGLUT expression boosts resilience while either too little or too much VGLUT leaves dopamine neurons more vulnerable to neurodegeneration.